Mammary gland development of prepubertal crossbred (Holstein x Gyr) heifers under different growth rates - Albino, Ronan Lopes (2016)
This work was designed to study the effect of performance levels during rearing on the mammary gland development of Holstein: Gyr (H: G) crossbred heifers; validate the ultrasound technique as a feasible tool to monitor instantaneously and non-invasive the parenchymal composition of mammary gland; describe surgical procedure for obtaining the parenchymal tissue samples from mammary glands of growing heifers.The work was performed in the Animal Science Department of Universidade Federal de Viçosa, Viçosa- MG. Eighteen crossbred heifers (H:G) with initial weight (102.2 ± 3,4kg) and aged between 3 and 4 months were evaluated over 84 days. Heifers were equally distributed (n = 6) between the high-gain treatments (HG, 1.0 kg / day), low gain (LG, 0.5 kg / day) and maintenance (MA).The difference in weight gain between treatments was achieved by the amount of feed offered using a single diet based on corn silage, soybean meal, soybean meal and minerals By Pass with roughage: concentrate ratio of 60:40.The body condition score (BCS), sampling of silage and leftovers were taken weekly. The heifer’s weight and ultrasonographic evaluation of the mammary gland were performed in 14 days intervals. The biometric measurements, blood samples and ultrasound on carcass were performed in 28 days intervals.In parallel, a biopsy was performed in mammary glands of heifers (3/treatment) at the beginning and middle of the experiment to obtain representative samples from the parenchymal tissue. At the end of the trial, all heifers were slaughtered and following biochemical, histological and gene expression analysis were performed in the mammary gland of each animal.The dry matter intake and other nutrients was higher for HG heifers when compared with LG and this, in turn, higher than MA, confirming the effectiveness of proposed treatments. Weight gain behaved similarly to intake, being highest gain for HG heifers (0.90 kg/d), 0.50 kg/d for BG and 0.10 kg/day MA.HG heifers showed higher BCS, subcutaneous fat thickness (SFT) and ribeye area (REA) in carcass evaluation when compared to other treatments. In ultrasonographic evaluation of the mammary gland there was a higher pixels concentration in HG mammary parenchyma than BG and MA, which did not differ from each other. HG heifers showed higher extra-parenchymal fat weight and higher concentration of ether extract in the parenchyma than BG and MA heifers. These results indicate, together, a higher concentration of fat in the parenchyma of animals under high weight gain. Regarding to histological evaluations in mammary parenchyma was observed higher percentage of area occupied by epithelial tissue in LG treatment than HG and MA. There was no difference in gene expression of IGF-1 between HG and LG treatments, but there was a greater expression of TGFR βI in HG.Thus, we concluded that heifers fed to show high weight gain, even with adequate level of protein in diet, accumulated more fat in mammary gland and had greater expression of genes that reduce epithelial growth.In the second study was conducted a regression analysis of pixels concentration in mammary parenchyma (fixed effect) in function of ether extract percentage in parenchyma (PAR), protein percentage in PAR, area occupied by epithelial tissue in PAR, number of adipocytes in the PAR, weight of extra-parenchymal fat and weight of parenchyma (random effect) to study the relationship between variables.At sequence, a sensitivity analysis was performed to determine the accuracy and precision of the equations found. Among the variables tested only PAR weight was not correlated with the pixel values in the parenchymal region. Between variables with significant correlation was observed high accuracy and from middle to high precision. Ultrasound images allowed identifying different growth patterns of mammary parenchymal tissue influenced by the level of performance of the heifers.Finally, it was described the procedures used to obtain samples of mammary parenchymal tissue in growing heifers. After sampling was carried out the RNA and DNA extraction from each PAR.Relation between RNA absorption (260 nm) and protein absorption (280 nm) analyzed the integrity of samples. The ratio greater than 1.80 indicated the quality of the RNA obtained.